Studi Kasus: Penggunaan Media Chatting Group dalam Pendampingan Masa Nifas Di TPMB Titin Widianingsih Pontianak - Dessy Hidayati Fajrin; Wella Sutrisnawati (Ovary Midwifery Journal, 2023)
The postpartum period is also known by another term puerperium which comes from the Latin word "puer" which means baby and "parous" which means giving birth. One of the important care objectives in the postpartum period is to provide postpartum health education. Postpartum education is given, among others, about postpartum care and breastfeeding, nutritional needs, birth spacing planning, breastfeeding process, immunizing the baby, healthy baby care and providing family planning services according to the mother's choice. However, there are still many postpartum mothers who do not get clear and accurate information related to postpartum midwifery care, so that in bridging the achievement of optimization in increasing knowledge about the postpartum period, it is very necessary to have a special application media for postpartum education to support the knowledge of postpartum women and the families who accompany them during the postpartum period. The research conducted used descriptive qualitative with a case study approach, and field observation. Midwifery care assessment in postpartum mothers is carried out basic data collection, namely subjective data and objective data. Subjective patient data includes: Mrs. R is PII A0, 23 years old, 3 days postpartum. Mrs. R said her breast milk had started to come out, felt helped by the Chatting Group so that she got information related to her health. Based on the results of the examination, objective data obtained Mrs. R's general condition is good, composmentis consciousness. Blood pressure 100/80 mmHg, pulse 74 x/min, regular. Breathing 22x/minute, regular. Temperature 36.3℃. On breast examination there is hyperpigmentation, no lumps, prominent nipples, no abscesses and swelling, there is milk release and the condition of the breasts is clean. TFU 2 fingers below the center, contractions are good, the vulva has no varicose veins, the perineal wound is clean and begins to dry out and release lokea rubra, PIIA0 Physiological Postpartum. With the Media Chatting Group, Mrs. R can undergo the postpartum period well without any obstacles.